Investing in mental health during the first 1,000 days of life: now and future - Bhamani, Shelina; Syed, Areeba; Sheikh, Lumaan; Mian , Ayesha (Journal of the Pakistan Medical Association, 2023)
Covid-19 has disrupted the mental health services in 93% of the countries worldwide. Approximately 130 countries are affected catastrophically by Covid-19, which limits access to mental health services. Most vulnerable are children, pregnant women, and adults with limited access to mental healthcare. In highlighting the importance of mobilising resources, the WHO has given leaders around the world an opportunity to galvanise efforts. Maternal and children’s mental health are crucial factors that may have a lifelong impact. In a post-pandemic world, a renewed focus is required to develop sustainable policies and action plans to support new mothers and new-borns in the first 1,000 days of life. This viewpoint shares a reflective discourse on contextualising the need of investment in mental health in times of crisis and global pandemic and what needs to be catered to in the near future. Keywords: First 1,000 days of life, Maternal health, Women’s health.